Evidence-based Guidelines for the Management of Exocrine Pancreatic Insufficiency After Pancreatic Surgery. Issue 6 (December 2016) - Sabater, Luis; Ausania, Fabio; Bakker, Olaf J.; Boadas, Jaume; Domínguez-Muñoz, J. Enrique; Falconi, Massimo; Fernández-Cruz, Laureano; Frulloni, Luca; González-Sánchez, Víctor; Lariño-Noia, José; Lindkvist, Björn; Lluís, Félix; et al.
Abstract : Supplemental Digital Content is available in the text Abstract : Objective: To provide evidence-based recommendations for the management of exocrine pancreatic insufficiency (EPI) after pancreatic surgery. Background: EPI is a common complication after pancreatic surgery but there is certain confusion about its frequency, optimal methods of diagnosis, and when and how to treat these patients. Methods: Eighteen multidisciplinary reviewers performed a systematic review on 10 predefined questions following the GRADE methodology. Six external expert referees reviewed the retrieved information. Members from Spanish Association of Pancreatology were invited to suggest modifications and voted for the quantification of agreement. Results: These guidelines analyze the definition of EPI after pancreatic surgery, (one question), its frequency after specific techniques and underlying disease (four questions), its clinical consequences (one question), diagnosis (one question), when and how to treat postsurgical EPI (two questions) and its impact on the quality of life (one question). Eleven statements answering those 10 questions were provided: one (9.1%) was rated as a strong recommendation according to GRADE, three (27.3%) as moderate and seven (63.6%) as weak. All statements had strong agreement. Conclusions: EPI is a frequent but under-recognized complication of pancreatic surgery. These guidelines provide evidence-based recommendations for the definition, diagnosis, and management of EPI after pancreatic surgery.